A Glance at Food Processing Applications - Var, Işıl; Uzunlu, Sinan (IntechOpen, 2022)
Food processing is a part of the manufacturing industry. To serve a marketable food product there are several intrinsic and extrinsic parameters to consider that determine the specific processing design of each product. Food production should ensure a safe, environmentally sustainable, and adequate supply of food. This book presents a comprehensive review of food processing applications. Chapters address such topics as the effects of rice bran, corn fiber, and sugarcane bagasse on the quality of baked foods, honey production processes, the potential usage of pectin in food packaging, and agro-industrial wastes for packaging processes, and much more.